Semantic analysis of Arabic language in chat communication and social media: Meaning shifts and formation of new terms - Nabilah, Farah Farhatun; Romadan, Alfi Nashrullah; Hasaniyah, Nur (Abjadia : International Journal of Education, 2025)
The shift in meaning and the formation of new terms in Arabic on social media and chat applications represent an important linguistic phenomenon in this digital age. This study aims to analyze how Arabic words undergo shifts in meaning and how new terms are formed through interactions on digital platforms. Using a literature review method, this research examines scholarly articles, books, and digital conversations from various sources such as WhatsApp and Instagram. The results show that communication via social media has driven changes in the meaning of everyday words, as well as the emergence of new terms often influenced by social, cultural, and globalization factors. Although this phenomenon enriches the Arabic language with new, more flexible, and expressive variations, there are also challenges in understanding word meanings, especially among generations not accustomed to digital language. The study concludes that the Arabic language in cyberspace continues to evolve in response to the demands of the times, although these changes may create difficulties in communication between generations. Further research is recommended to explore the impact of these changes on the structure of formal language and Arab cultural identity.